Articulación de resistencias a la expansión forestal en Uruguay y Argentina - Ramirez, Delia Concepción (2024)
Piray 18 in Misiones (Argentina) and Paso Centurión in Cerro Largo (Uruguay) represent significant experiences of populations that managed to stop the advance of forestry. At the regional level, it has influenced the consolidation of foreign ownership and concentration of land ownership. The contexts also converge: these are areas considered productively marginal, on national borders (with Brazil and Paraguay), where hybrid forms of the national language (Spanish) coexist with subaltern languages (Jopará and Portuñol). The investigation of the subaltern politicization of local actors allows a different view of the hegemonic processes of economic, social and territorial transformation, based on the challenge to the development model installed in the policies of business promotion. The right to inhabit the territories and to a healthy environment is re-signified from these collective experiences and what we call environmental narrative is presented as a strategic resource of the actors in conflict to position themselves in opposition to forest agribusiness and to carry out strategic actions accordingly.